Shock Wave Physics as Related to Primary Non-Impact Blast-Induced Traumatic Brain Injury. (25th January 2021) - Rutter, Barbara; Song, Hailong; DePalma, Ralph G; Hubler, Graham; Cui, Jiankun; Gu, Zezong; Johnson, Catherine E
ABSTRACT: Introduction: Blast overpressure exposure, an important cause of traumatic brain injury (TBI), may occur during combat or military training. TBI, most commonly mild TBI, is considered a signature injury of recent combat in Iraq and Afghanistan. Low intensity primary blast-induced TBI (bTBI), caused by exposure to an explosive shock wave, commonly leaves no obvious physical external signs. Numerous studies have been conducted to understand its biological effects; however, the role of shock wave energy as related to bTBI remains poorly understood. This report combines shock wave analysis with established biological effects on the mouse brain to provide insights into the effects of shock wave physics as related to low intensity bTBI outcomes from both open-air and shock tube environments. Methods: Shock wave peak pressure, rise time, positive phase duration, impulse, shock velocity, and particle velocity were measured using the Missouri open-air blast model from 16 blast experiments totaling 122 mice to quantify physical shock wave properties. Open-air shock waves were generated by detonating 350-g 1-m suspended Composition C-4 charges with targets on 1-m elevated stands at 2.15, 3, 4, and 7 m from the source. Results: All mice sustained brain injury with no observable head movement, because of mice experiencing lower dynamic pressures than calculated in shock tubes. Impulse, pressure loading over time, was found to be directly related to bTBI severity and is a primary shock physics variable that relates to bTBI. Discussion: The physical blast properties including shock wave peak pressure, rise time, positive phase duration, impulse, shock velocity, and particle velocity were examined using the Missouri open-air blast model in mice with associated neurobehavioral deficits. The blast-exposed mice sustained ultrastructural abnormalities in mitochondria, myelinated axons, and synapses, implicating that primary low intensity blast leads to nanoscale brain damage by providing the link to its pathogenesis. The velocity of the shock wave reflected back from the target stand was calculated from high-speed video and compared with that of the incident shock wave velocity. Peak incident pressure measured from high sample rate sensors was found to be within 1% of the velocity recorded by the high-speed camera, concluding that using sensors in or close to an animal brain can provide useful information regarding shock velocity within the brain, leading to more advanced knowledge between shock wave physics and tissue damage that leads to bTBIs.